2009
DOI: 10.1007/s13199-009-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ectomycorrhizal fungus Laccaria laccata on pre-emergence, post-emergence and late damping-off by Fusarium oxysporum and F. verticillioides on Stone pine seedlings

Abstract: In greenhouse experiments, the ectomycorrhizal fungus Laccaria laccata was evaluated for biological control of preemergence, post-emergence and late damping-off of Pinus pinea caused by Fusarium verticillioides and F. oxysporum. In pre-emergence damping-off assays, preinoculation with Laccaria laccata did not significantly improve germination of seeds and no statistical significant differences were found in Fusarium treatments when compared with controls. At 18 weeks after sowing, inoculation with L. laccata r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 34 publications
5
32
0
2
Order By: Relevance
“…The isolate was selected because previous research confirmed its high virulence on Pinus sylvestris (Machón et al, 2006). The isolate was long-term maintained on Komada (K) medium (Komada, 1975).…”
Section: Fungal Pathogens and Inoculum Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolate was selected because previous research confirmed its high virulence on Pinus sylvestris (Machón et al, 2006). The isolate was long-term maintained on Komada (K) medium (Komada, 1975).…”
Section: Fungal Pathogens and Inoculum Preparationmentioning
confidence: 99%
“…Basándonos en los cambios morfológicos observados en las plántulas de 6 meses de P. pinaster (reducción del creci-2010; Kim et al, 2010). Worldwide, damping off caused by Fusarium oxysporum is probably one the most severe disease affecting seedlings in forest nurseries (Machón et al, 2006). In south-western Europe, the pitch canker and the Dutch elm disease, caused by F. circinatum and O. novo-ulmi respectively, are amongst the problems causing higher impact in forests (Martín et al, 2008a, b;Vivas et al, 2012) and none of the suggested control strategies have been effective, either for technical, economical, or environmental limitations.…”
mentioning
confidence: 99%
“…The most common genera associated with the pathology are Phytophthora, Pythium, Fusarium and Rhizoctonia (Camporota and Perrin, 1998;Gordon et al, 2015). Some strains of the Fusarium genus have been reported as causal agents of damping-off in seedlings of the Pinus genus, including P. nigra and P. pinea (Martín-Pinto et al, 2006;Machón et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cooke (Strobel and Sinclair 1991;Chakravarty and Hwang 1991;Branzanti et al 1999;Machón et al 2006Machón et al , 2009, or the poisonous Paxillus involutus Pedersen et al 1999). However, there is a lack of research about the effects of edible mushrooms with commercial cultivation interest against damping-off (but see Zhang et al 2011).…”
Section: Grown In Containersmentioning
confidence: 99%
“…The control mechanism involves total or partial elimination of the pathogen population, or the reduction of damaging effects on plants (Cook and Baker 1996). Several authors have suggested that biological control with ectomycorrhizal fungi (ECM) may be feasible for controlling damping-off as an alternative or a complement to fungicides (Hwang et al 1995;Pedersen et al 1999;Machón et al 2006Machón et al , 2009Zhang et al 2011). However, the effectiveness of ECM in disease suppression may depend both on particular mycorrhizal and host species, as well as soil conditions (Sampagni et al 1985).…”
Section: Introductionmentioning
confidence: 99%